Impact Of E-Learning-Based Cooperative Learning Activities On Achievement And Communication Skills As Perceived By Undergraduate Students In Qatar University - Ahmed, Mahmood Ahmed Hassan (2012)
This research aims to investigate the impact of e-learning-based cooperative learning on students’ achievement in the Arabic Language Course (ARAB100) and their perceptions of communication skills. E-learning modules were developed by the researcher with a panel of experts and delivered through the Blackboard system at Qatar University, State of Qatar. The achievement test and communication skills questionnaire as perceived by students were also developed and administered to four sections of the Arabic Language Course (ARAB100) before and after the treatment.